Bioenergy Industry Management Challenges and Opportunities in the Energy Transition Era - Gede Arya Rachman; Syukri M. Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
The era of global energy transition has positioned bioenergy as a critical component in diversifying renewable energy sources. This study aims to analyze the implementation of bioenergy industry management in the context of energy transition, with a focus on the development of an integrated risk management framework and operational optimization. Through a systematic literature review (SLR) approach to publications from the 2019-2024 period from the Scopus, Web of Science, Science Direct, and ProQuest databases, this study integrates findings from 247 selected articles. The results of the analysis show a significant increase in operational efficiency of up to 45% through the implementation of an integrated risk management framework, including a real-time monitoring system and an AI-based decision-making platform. The financial impact analysis reveals a reduction in OPEX of 34.4% and an increase in CAPEX ROI from 15.3% to 22.8%. From an environmental perspective, the implementation of the framework has succeeded in reducing CO2e emissions by 36.5% and water use by 25%. This study identifies four main challenges in implementation: technology gaps, supply chain complexity, immature regulatory frameworks, and the need for human resource development. The developed framework integrates technical, economic, and social aspects, providing practical guidance for the industry in the transition to sustainable bioenergy. This research contributes to the development of theoretical framework and practical guidelines for bioenergy industry management, while opening up new research opportunities in the integration of blockchain, IoT, and advanced AI technologies for operational optimization. The results show that continuous evolution in the management approach of the bioenergy industry is key to realizing an effective and sustainable energy transition.